A SatuSehat Compliant FHIR R4 ECG Implementation Guide: Bridging Clinical and Informatics Domains in Indonesia - Thomas Adhi Nugroho Chaidir; David Habsara Hareva (Universitas Komputer Indonesia, 2025)
Indonesia’s SatuSehat mandates HL7 FHIR R4 interoperability, yet limited informatics capacity creates clinical-software translation gaps. This study develops and validates a SatuSehat-compliant electrocardiogram (ECG) data model and API contract via a FHIR Implementation Guide (IG). We mapped the HL7 aECG v1 standard to FHIR R4 using a six-phase normative workflow. From 312 aECG attributes, 17 defined the core exchange surface, fully supporting standard 12-lead ECGs. Although SNOMED CT only covered 13 of 32 lead types, missing specialized leads were addressed using provisional ValueSets. The resulting computable IG enables standardized, scalable ECG data exchange via FHIR REST and Bulk Data export, effectively bridging clinical requirements with technical implementation in resource-limited settings.